Analysis of Misconceptions in the 2023 Revised Edition of 4th Grade Elementary School Science Textbook - Fakhriyah*, Fina; Syukur, Ahmad; Aminah, Siti Khalimatul; Ratnasari, Yuni; Roslan, Roslinawati (Jurnal IPA & Pembelajaran IPA, 2025)
Identifying misconceptions in the 2023 revised edition of the natural and social sciences (IPAS) of 4th grade book published by the Indonesian Ministry of Education and Culture is the aim of this research. Qualitative descriptives were implemented in this research with a content analysis strategy. The 2023 revised edition of the 4th grade natural dan social sciences book published by the Indonesian Ministry of Education and Culture is used as a source of study data. The level of misconception category consists of misidentification, overgeneralization, oversimplification, obsolete concept and term and under generalizations. Based on the research carried out, the results showed that there were misconceptions about the material in the 2023 revised edition of the 4th grade natural dan social sciences book. In the overgeneralization category there are 4 concepts, namely photosynthesis, changes in forms of energy, muscle force and the greenhouse effect. In the oversimplifications category, there are 4 concepts, namely photosynthesis, muscle force, magnetic force and gravitational force